Hirsutine, an Indole Alkaloid of Uncaria rhynchophylla, Inhibits Late Step in Dengue Virus Lifecycle - Hishiki, Takayuki; Kato, Fumihiro; Tajima, Shigeru; Toume, Kazufumi; Umezaki, Masahito; Takasaki, Tomohiko; Miura, Tomoyuki (Frontiers in Microbiology, 2017)
Dengue virus (DENV) is transmitted to humans by Aedes mosquitoes, and is a public health issue worldwide. No antiviral drugs specific for treating dengue infection are currently available. To identify novel DENV inhibitors, we analyzed a library of 95 compounds and 120 extracts derived from crude drugs (herbal medicines). In the primary screening, A549 cells infected with DENV-1 were cultured in the presence of each compound and extract at a final concentration of 10 μM (compound) and 100 μg/mL (extract), and reduction of viral focus formation was assessed. Next, we eliminated compounds and extracts which were cytotoxic using the MTT assay. Hirsutine, an indole alkaloid of Uncaria rhynchophylla, was identified as a potent anti-DENV compound exhibiting high efficacy and low cytotoxicity. Hirsutine showed antiviral activity against all DENV serotypes. Time-of-drug-addition and time-of-drug-elimination assays indicated that hirsutine inhibits the viral particle assembly, budding, or release step but not the viral translation and replication steps in the DENV lifecycle. A subgenomic replicon system was used to confirm that hirsutine does not restrict viral genome RNA replication. Hirsutine is a novel DENV inhibitor and potential candidate for treating dengue fever.